Long-term effects of cyclophosphamide and colchicine treatment in Behçet's disease. - (:unkn) unknown (My University, 1991)
We assessed the long-term effects of cyclophosphamide and colchicine on visual prognosis and attack frequency in 64 patients with Behcet's disease who were studied in two separate groups between the years of 1976 and 1989. No statistically significant positive changes in visual acuity or attack frequency which might be attributed to the treatment could be shown when the period of treatment was compared with the period after treatment.